Towards a Circular Bioeconomy in Cacao Bean Shells: Recent Valorization Pathways and Potential Applications in Food Powder Formulations–A Review - Philip Donald C Sanchez; Norhashila Hashim; Mohd Salahuddin Mohd Basri; Nazamid Bin Saari; Dimas Rahadian Aji Muhammad (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Cacao bean shells (CBS), a by-product of chocolate production known for their rich content of bioactive, nutritional, and functional compounds, have gained increasing attention in recent years as part of circular bioeconomy strategies. In the framework of valorization, CBS has been widely explored for diverse applications, including as a fuel, feed, fiber, and nutraceuticals. However, despite its industrial potential, no comprehensive review has yet addressed its valorization pathways, particularly its viability as an ingredient in food powder formulations. Therefore, this review examines the potential of CBS as a food powder resource and evaluates its feasibility as functional ingredient in food systems, focusing on formulation techniques, processing technologies, and the assessment of techno-functional properties. This comprehensive review further examines the potential utilization of CBS powder in food formulations and its corresponding feasibility as an admixture for premix powder formulations. The findings indicate that the valorization of CBS powder in food formulations remains largely unexplored, with only a limited number of studies investigating its application in baked systems. Overall, this review highlights significant opportunities for further exploration of CBS valorization, particularly its potential as an admixture in instant premix powder formulations, as current applications primarily rely on direct incorporation. This review serves as foundational knowledge for food processors and researchers committed to circular economy principles, with a strong interest in the development of innovative food products derived from CBS powder.